Analisis Kinerja Sistem Informasi Akuntansi CV. Dharma Aksara - Adelia Mega Purnamawati; Pardi Pardi (STIE Widya Manggala, 2022)
This research with aim determine the influence of impact of users, capability of person, organization, funding, and information technology on performance accounting system information of CV. Dharma Aksara still used accounting information system manual basic with use 50 samples from 117 active employees. This analizing method used was multiplied analysis linear regression classic hypotheses testing consists of test,1) f test, and coefficient of determination test, 2) assumption tests including normality, 3) multicollinearity, and 4) heteroscedasticity tests. The result appear influence of impact of users and capability of person take effect for performance accounting system information being directly involved with the use of performance accounting system information. Funding take effect to for performance accounting system information being for the maintenance of system equipment that supports the running of the accounting information system, and daya technology conclusion performance accounting system information because the operating system is inputting dataand processing data using computerized technology but organization hasn’t conclusion withperformance accounting system information due to the high individualism of employees per division in the company